2019
DOI: 10.1371/journal.pone.0224749
|View full text |Cite
|
Sign up to set email alerts
|

The impact of “male clinics” on health-seeking behaviors of adult men in rural Kenya

Abstract: BackgroundIn most parts of the world, men access health services less frequently than women, and this trend is unrelated to differences in need for services. While male involvement in healthcare as partners or fathers has been extensively studied, less is known about the health-seeking behavior of men as clients themselves. This interventional research study aimed to determine how the introduction of male-friendly clinics impacted male care-seeking behavior and to describe the reasons for accessing services am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…While the provision of private spaces for the delivery of services may be a practical consideration, it may be impossible to achieve since such levels of privacy may not be available in public health settings. The findings from Dowden et al (2019) demonstrate that the provision of privacy with an emphasis on health rather than a disease focus may be more attractive to men in increasing access to “male sensitive” services. Furthermore, men want to access health services in health settings but place a high value on maintaining anonymity although his very presence in the facility may be an indication that he was in need of help.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the provision of private spaces for the delivery of services may be a practical consideration, it may be impossible to achieve since such levels of privacy may not be available in public health settings. The findings from Dowden et al (2019) demonstrate that the provision of privacy with an emphasis on health rather than a disease focus may be more attractive to men in increasing access to “male sensitive” services. Furthermore, men want to access health services in health settings but place a high value on maintaining anonymity although his very presence in the facility may be an indication that he was in need of help.…”
Section: Discussionmentioning
confidence: 99%
“…Since being a man and how men performed masculinity is based on social contexts, it provides even greater challenges in attempting to define “male sensitive” health services (Bardehle et al, 2016). Dowden et al (2019) intervention which provided male health care workers in separate clinical spaces proved an effective strategy in increasing uptake of health services since it reduced stigma and reduced waiting times for men. While researchers agree that men are not a homogenous group it may not be possible to develop a health service that can be construed as meeting the needs of all men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of social, behavioural and physical factors, and health systems challenges provides a better understanding of barriers men face in accessing health services for their sexual and reproductive health needs [ 18 , 26 , 27 ]. However, when there are services dedicated to men, studies have shown that there is an increase in health seeking behaviours [ 28 ], that underscores the great potential of self-care strategies in increasing safe and private sexual and reproductive health and rights options for men.…”
Section: Proposing Research Considerations For Self Care In Men’s Sexmentioning
confidence: 99%